CONVERSION TO OPEN CHOLECYSTECTOMY - A SAFE ALTERNATIVE, NOT A FAILURE! - Singh, Gaurav; Behari, Anu; Prakash, Anand; Singh, Rajneesh Kumar; Gupta, Ashok Kumar; Kapoor, Vinay K; Saxena, Rajan (International Journal of Research -GRANTHAALAYAH, 2024)
Background: Understanding factors that predict conversion in laparoscopic cholecystectomy (LC) to an open procedure is important as it allows better patient selection, preparation, operating list planning, referral, counseling and lowers the threshold for a safe conversion, thereby minimizing undue prolongation of attempts at laparoscopic completion and inadvertent complications. Methods: Records of 1010 consecutive patients who were taken up for LC, at a tertiary care teaching institute in northern India, were reviewed retrospectively. Preoperative and intraoperative characteristics of patients who underwent a successful LC were compared with those who required conversion to open surgery. Results: The conversion rate was 7.5% (76 patients). The most common reason for conversion was the inability to define the ‘Critical view of safety’ in 48, (63%) of patients. Other reasons included dense peri-cholecystic 9 (12%) and intra-abdominal 8 (11%) adhesions, suspicion of bile duct injury 4 (5%) or malignancy 3 (4%). Prior upper abdominal surgery, intraoperative finding of a contracted and thick-walled gallbladder (GB), empyema GB, Mirizzi’s syndrome, cholecysto-enteric fistula, and a prior endoscopic common bile duct stone clearance were significant predictors of conversion. Xanthogranulomatous cholecystitis was found more commonly (43% vs 5%) in the conversion group. Conclusion: Conversion to an open procedure during LC should always be treated as an integral component of sound judgement to achieve the safest outcome in a particular patient. Due consideration of pre-operative and intra-operative factors predictive of a higher chance of conversion assists pre-operative patient preparation and counseling as well as surgical planning, conduct and mentoring of residents-in-training.